Evidence summaries and recommendations from the international evidence‐based guideline for the assessment and management of polycystic ovary syndrome: Lifestyle management. (26th May 2020) - Moran, Lisa J.; Tassone, Eliza C.; Boyle, Jacqueline; Brennan, Leah; Harrison, Cheryce L.; Hirschberg, Angelica Lindén; Lim, Siew; Marsh, Kate; Misso, Marie L.; Redman, Leanne; Thondan, Mala; Wijeyaratne, Chandrika; et al.
Summary: Lifestyle is fundamental in chronic disease prevention and management, and it has been recommended as a first‐line treatment in the Australian polycystic ovary syndrome (PCOS) guideline 2011. The first international evidence‐based guideline on PCOS was developed in 2018, which expanded the scope and evidence in the Australian guideline. This paper summarizes the lifestyle recommendations and evidence summaries from the guideline. International multidisciplinary guideline development groups delivered the International Evidence‐based Guideline for the Assessment and Management of Polycystic Ovary Syndrome 2018. The process followed the Appraisal of Guidelines for Research and Evaluation II and The Grading of Recommendations, Assessment, Development and Evaluation framework. Extensive communication and meetings addressed six prioritized clinical questions through five reviews. Evidence‐based recommendations were formulated before consensus voting within the panel. Evidence shows the benefits of multicomponent lifestyle intervention, efficacy of exercise and weight gain prevention with no specific diet recommended. Lifestyle management is the first‐line management in the intervention hierarchy in PCOS. Multicomponent lifestyle intervention including diet, exercise and behavioural strategies is central to PCOS management with a focus on weight and healthy lifestyle behaviours. The translation programme optimizes reach and dissemination for health professionals and consumers.